The American century the rise and decline of the United States as a world power - White, Donald W. (Yale Univ. Press, 1996)
"Explores what Americans thought about power in the twentieth century, how they evaluated America's expanding world role and the confrontations of the Cold War, and how they perceived the erosion of this unprecedented accumulation of power in the years after the Vietnam War."--Jacket.